Pendidikan Berbasis Teknologi : (Permasalahan dan Tantangan) - Fitri Kurnia (Tarbawi : Jurnal Studi Pendidikan Islami, 2022)
Educational technology is designed to help solve educational problems, so that it can provide benefits in efforts to improve the quality of learning. Various forms of learning experiences, both those that can be achieved in the classroom and outside the classroom and learning messages, can be packaged by paying attention to the rules and principles of educational technology. With the use of learning technology, it is hoped that educational messages can be packaged more systematically, both in physical packaging and virtual, which is no longer limited by the dimensions of space or time, so that it can be accepted by students well, easily and widely, and creates education that is fun, flexible in the dimensions of time, space, and develops the potential of individual students. Apart from providing benefits, technology in the education sector also provides several obstacles that have a positive impact on education.